3 Malaysian universities in top 100 world universities ranking - Borneo Post, (Kuching) (Borneo Post (Kuching), 2016)
KUALA LUMPUR: Three Malaysian universities made it to the top 100 list out of the 300 universities, involving 50 countries, of the Times Higher Education (THE) BRICS and Emerging Economies University Rankings 2017.